2019
DOI: 10.3390/molecules24162966
|View full text |Cite
|
Sign up to set email alerts
|

Soy Isoflavones Improve the Spermatogenic Defects in Diet-Induced Obesity Rats through Nrf2/HO-1 Pathway

Abstract: Soy isoflavones (SIF) are biologically active compounds of non-steroidal and phenolic properties that are richly present in soybeans, which can reduce the body weight and blood lipids of obese animals. Recently, SIF have been reported to affect reproductive ability in obese male rats. However, the specific mechanism has not been well defined. The aim of the current study was to study the possible mechanisms for the effect of SIF administration on obesity induced spermatogenic defects. Obese rats model induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 71 publications
3
11
1
Order By: Relevance
“…Testicular MDA, and glutathione content, catalase activity and expression of genes involved in oxidative stress were not significantly affected by the HFD feeding protocol in the current study. This is in contrast to previous studies reporting increased MDA content, expression of NFκB-p65, IL6 and TNF-α gene, decreased glutathione content, catalase activity and expression of Nrf2 and IL10 gene in testis of HFD-fed rodents [ 3 , 4 , 42 44 ]. However, the investigation of mRNA and protein expression of Nrf2, NFκB-p65, IL6, IL10 and TNF-α in seminal plasma would be of future interest given the altered cytokine levels in seminal plasma induced by HFD in a recent study [ 59 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Testicular MDA, and glutathione content, catalase activity and expression of genes involved in oxidative stress were not significantly affected by the HFD feeding protocol in the current study. This is in contrast to previous studies reporting increased MDA content, expression of NFκB-p65, IL6 and TNF-α gene, decreased glutathione content, catalase activity and expression of Nrf2 and IL10 gene in testis of HFD-fed rodents [ 3 , 4 , 42 44 ]. However, the investigation of mRNA and protein expression of Nrf2, NFκB-p65, IL6, IL10 and TNF-α in seminal plasma would be of future interest given the altered cytokine levels in seminal plasma induced by HFD in a recent study [ 59 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Several rodent studies reported similar sperm and/or testicular oxidative damage as well as testicular weight upon feeding HFD [ 3 , 5 , 6 , 42 46 ] as we have demonstrated here. However, limited work has examined the effects of supplementation with the micronutrients used in this study (single or combined) on HFD-induced oxidative damage in both sperm and testis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Oxidative stress, which is the major reason for male infertility, has gained importance recently (5). Oxidative imbalance occurs when the balance between oxidant and antioxidant systems is impaired.…”
Section: Introductionmentioning
confidence: 99%
“…Soy isoflavones administration normalized metabolic and immunological parameters via oxidative stress amelioration in female rats [ 27 ]. In male rats, soy isoflavones treatment (150 and 450 mg/kg of body weight per day for 4 weeks) showed a protective effect against HFD-induced testicular oxidative stress, cell apoptosis, and associated tissue damage [ 28 ]. As previously mentioned, soy isoflavone treatment supports the alleviation of exercise-induced oxidative stress, partially via enhancement of antioxidant enzyme activities [ 29 ].…”
Section: Discussionmentioning
confidence: 99%